Desulfovibrio is not always associated with adverse health effects in the Guangdong Gut Microbiome Project - Chen, Yi-ran; Jing, Qin-long; Chen, Fang-lan; Zheng, Huimin; Chen, Li-dan; Yang, Zhi-cong (PeerJ, 2021)
Desulfovibrio (DSV) is frequently found in the human intestine but limited knowledge is available regarding the relationship between DSV and host health. In this study, we analyzed large-scale cohort data from the Guangdong Gut Microbiome Project to study the ecology of DSV and the associations of DSV and host health parameters. Phylogenetic analysis showed that Desulfovibrio piger might be the most common and abundant DSV species in the GGMP. Predominant sub-OTUs of DSV were positively associated with bacterial community diversity. The relative abundance of DSV was positively correlated with beneficial genera, including Oscillospira, Coprococcus,Ruminococcus,Akkermansia, Roseburia,Faecalibacterium, andBacteroides, and was negatively associated with harmful genera, such as Clostridium,Escherichia,Klebsiella, and Ralstonia. Moreover, the relative abundance of DSV was negatively correlated with body mass index, waist size, triglyceride levels, and uric acid levels. This suggests that DSV is associated with healthy hosts in some human populations.
Keywords: Desulfovibrio; Gut microbiota; Correlation; Host parameters; Microbial community